2003
DOI: 10.1074/jbc.m307760200
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Hydroperoxides Activate the Mitogen-activated Protein Kinase Mpk1p in Saccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae is capable of responding to oxidants, including lipid peroxidation products. We investigate here the role of the mitogen-activated protein kinase Mpk1p in protection against linoleic acid hydroperoxide (LoaOOH), a product of radical attack on an unsaturated lipid. MPK1 was found to be required for resistance to LoaOOH. Furthermore, Mpk1p was rapidly and transiently phosphorylated in response to LoaOOH. This phosphorylation was dose-dependent and stimulated by sublethal concentrations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 47 publications
5
28
0
1
Order By: Relevance
“…In particular, the mechanisms underlying the involvement of the GPI-CWP Spi1p, examined in the present study, in yeast response to stress certainly deserve attention. In fact, the inspection of results from microarray analysis obtained in recent years reveals that SPI1 transcription, together with the transcription of other genes encoding proteins that have a structural role in cell architecture, is activated in response to a number of environmental stress conditions, including osmotic stress, lipid peroxidation, low external pH, stress induced by the herbicide 2,4-D, and heat stress (2,4,14,15,23,25,29). SPI1 is also up-regulated in response to cell wall-destabilizing conditions, involving cell wall mutations or the application of hydrolytic enzymes such as Zymolyase (13,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the mechanisms underlying the involvement of the GPI-CWP Spi1p, examined in the present study, in yeast response to stress certainly deserve attention. In fact, the inspection of results from microarray analysis obtained in recent years reveals that SPI1 transcription, together with the transcription of other genes encoding proteins that have a structural role in cell architecture, is activated in response to a number of environmental stress conditions, including osmotic stress, lipid peroxidation, low external pH, stress induced by the herbicide 2,4-D, and heat stress (2,4,14,15,23,25,29). SPI1 is also up-regulated in response to cell wall-destabilizing conditions, involving cell wall mutations or the application of hydrolytic enzymes such as Zymolyase (13,19).…”
Section: Discussionmentioning
confidence: 99%
“…Global expression analysis carried out in recent years has indicated that yeast cells respond to environmental stress by modifying the organization of the cell wall (13,19). This cell remodeling may compensate for the damage produced in the cell wall, may increase protection against diverse stresses, and may result in the rapid induction of resistance to cell wall-lytic enzymes (2,4,8,13,14,15,23,25,28,29). Nevertheless, the specific role of cell wall-associated proteins in this stress response and their contribution to the development of stress resistance remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Current understanding of each of the inputs and outputs of this pathway related to the maintenance of cell wall integrity will be discussed individually. Although the CWI pathway has additionally been implicated in the responses to oxidative stress (Alic et al 2003;Vilella et al 2005), high and low pH stress (Claret et al 2005;Serrano et al 2006), and DNA damage (Queralt and Igual 2005;Dardalhon et al 2009;Truman et al 2009;Bandyopadhyay et al 2010), this review article will be restricted to its role in the maintenance of cell wall integrity.…”
Section: Overview Of Cwi Signalingmentioning
confidence: 99%
“…For instance, stretching of the plasma membrane, hypo-osmotic shock, exposure to the wall-degrading enzyme preparation Zymolyase or to wall-perturbing compounds such as calcofluor white, which binds chitin, and Congo red, which preferentially perturbs wall construction in the neck region (29), lead to activation of the CWI pathway (17,26,42,47). Another trigger is oxidative stress (4,47). Upon alterations in the fungal wall, plasma membrane-bound sensor proteins get activated and trigger mitogen-activated protein kinase (MAPK) signaling cascades that end in the activation of tran-scription factors involved in wall maintenance.…”
mentioning
confidence: 99%